Low 2-Year All-Cause Mortality and Major Stroke Rates after CoreValve Implantation - Rizzo, Toni (MD Conference Express, 2014)
The Safety and Efficacy Study of the Medtronic CoreValve System in the Treatment of Symptomatic Severe Aortic Stenosis in High-Risk and Very High-Risk Subjects Who Need Aortic Valve Replacement [CoreValve; NCT01240902] evaluated transcatheter aortic valve replacement using a self-expanding bioprosthesis in patients with severe aortic stenosis at extreme risk for surgery.